Fundamentals of English grammar interactive - Azar, Betty Schrampfer ([New York] : Pearson Longman, 2007)
This cd-rom combines the best instruction and practice in one program includes lively grammar presentations, extensive grammar practice, learner support and ongoing assessment
Guide to use this CD: 1. Need pc that connected with Internet. 2. Install the program by follow the instruction given. 3. Click the icon at the desktop to use this program
Single user version
Installation process required PC connected with internet and the accessing program by browser Internet Explorer
System requirements: Windows XP, Windows 2000 with Service Pack 4; Non-English Windows 2000 systems require the Professional edition; Pentium II processor 400+ MHz; 128+ MB RAM (256 MB recommended); 16-bit graphics card; monitor resolution of 800 x 600 or higher; sound card, microphone, and speakers; 10X CD-ROM drive; disk space or saving student data (floppy, flash memory, hard drive); Internet Explorer 6.0 (Netscape and AOL browser software are not supported); Macromedia's Flash 8 plug-in or Internet connection; Sun's Java 1.5.0_06 plug-in (If your computer does not have this plug-in, it will be installed automatically when you install the course)
Keywords: English language -- Grammar -- Problems, exercises, etc; English language -- Textbooks for foreign speakers